Co-regulation of the copper vacancy concentration and point defects leading to the enhanced thermoelectric performance of Cu3In5Te9-based chalcogenides. Issue 54 (7th October 2019) - Li, Min; Luo, Yong; Hu, Xiaojuan; Han, Zhongkang; Liu, Xianglian; Cui, Jiaolin
Abstract : Co-regulation of both the copper vacancy concentration ( V c ) and point defect GaIn realizing the high carrier concentration and low lattice thermal conductivity in Cu3 In5 Te9 -based chalcogenides simultaneously. Abstract : Copper vacancy concentration ( V c ) in ternary Cu–In–Te chalcogenides is an important factor to engineer carrier concentration ( n H ) and thermoelectric performance. However, it is not sufficient to regulate the phonon scattering in the Cu3 In5 Te9 -based chalcogenides. In this work we manipulate the V c value and point defects simultaneously through addition of Cu along with Ga substitution for In in Cu3 In5 Te9, and thereby increase the carrier concentration and reduce the lattice thermal conductivity. This strategy finally enables us to achieve ∼60% enhancement of the TE figure of merit ( ZT ) at V c = 0.078 compared with the pristine Cu3 In5 Te9 . It is also used as guidance to achieve the high TE performance of the ternary chalcogenides.